An indirect comparison and cost per responder analysis of adalimumab, methotrexate and apremilast in the treatment of methotrexate-naïve patients with psoriatic arthritis. (2nd April 2016) - Betts, Keith A.; Griffith, Jenny; Friedman, Alan; Zhou, Zheng-Yi; Signorovitch, James E.; Ganguli, Arijit
Abstract: Objective Apremilast was recently approved for the treatment of active psoriatic arthritis (PsA). However, no studies compare apremilast with methotrexate or biologic therapies, so its relative comparative efficacy remains unknown. This study compared the response rates and incremental costs per responder associated with methotrexate, apremilast, and biologics for the treatment of active PsA. Methods A systematic literature review was performed to identify phase 3 randomized controlled clinical trials of approved biologics, methotrexate, and apremilast in the methotrexate-naïve PsA population. Using Bayesian methods, a network meta-analysis was conducted to indirectly compare rates of achieving a ≥20% improvement in American College of Rheumatology component scores (ACR20). The number needed to treat (NNT) and the incremental costs per ACR20 responder (2014 US$) relative to placebo were estimated for each of the therapies. Results Three trials (MIPA for methotrexate, PALACE-4 for apremilast, and ADEPT for adalimumab) met all inclusion criteria. The NNTs relative to placebo were 2.63 for adalimumab, 6.69 for apremilast, and 8.31 for methotrexate. Among methotrexate-naïve PsA patients, the 16 week incremental costs per ACR20 responder were $3622 for methotrexate, $26, 316 for adalimumab, and $45, 808 for apremilast. The incremental costs per ACR20 responder were $222, 488 for apremilast vs. methotrexate. Conclusion Among methotrexate-naive PsA patients, adalimumab was found to have the lowest NNT for one additional ACR20 response and methotrexate was found to have the lowest incremental costs per ACR20 responder. There was no statistical evidence of greater efficacy for apremilast vs. methotrexate. A head-to-head trial between apremilast and methotrexate is recommended to confirm this finding.